Electrophysiological properties of human beta-cell lines EndoC-βH1 and -βH2 conform with human beta-cells. Issue 1 (December 2018) - Hastoy, Benoît; Godazgar, Mahdieh; Clark, Anne; Nylander, Vibe; Spiliotis, Ioannis; Bunt, Martijn; Chibalina, Margarita; Barrett, Amy; Burrows, Carla; Tarasov, Andrei; Scharfmann, Raphael; Gloyn, Anna; et al.
Abstract Limited access to human islets has prompted the development of human beta cell models. The human beta cell lines EndoC-βH1 and EndoC-βH2 are increasingly used by the research community. However, little is known of their electrophysiological and secretory properties. Here, we monitored parameters that constitute the glucose-triggering pathway of insulin release. Both cell lines respond to glucose (6 and 20 mM) with 2- to 3-fold stimulation of insulin secretion which correlated with an elevation of [Ca2+ ]i, membrane depolarisation and increased action potential firing. Similar to human primary beta cells, KATP channel activity is low at 1 mM glucose and is further reduced upon increasing glucose concentration; an effect that was mimicked by the KATP channel blocker tolbutamide. The upstroke of the action potentials reflects the activation of Ca2+ channels with some small contribution of TTX-sensitive Na+ channels. The repolarisation involves activation of voltage-gated Kv2.2 channels and large-conductance Ca2+ -activated K+ channels. Exocytosis presented a similar kinetics to human primary beta cells. The ultrastructure of these cells shows insulin vesicles composed of an electron-dense core surrounded by a thin clear halo. We conclude that the EndoC-βH1 and -βH2 cells share many features of primary human β-cells and thus represent a useful experimental model.